Israel : Detailed Assessment of Observance of International Association of Insurance Supervisors Insurance Core Principles. (IMF Staff Country Reports; Country Report ;, 2012)
A full assessment of Israel's compliance with the Insurance Core Principles (ICPs) of the International Association of Insurance Supervisors (IAIS) is presented. The Minister of Finance bears the political responsibility for supervisory oversight of the Israeli insurance system. Nonlife insurance accounts for about 50 percent of total premiums in the country, and motor premiums make up about 50 percent of that total. The Israeli insurance sector has been hit hard by the financial crisis. The Israeli stock market has fallen by 51 percent, sharply impacting companies' earnings in 2008.